EFFECT PICTURE AND PICTURE MODELS ASSISTED BY PUZZLE ON COGNITIVE LEARNING OUTCOMES STUDENT KINGDOM ANIMALIA MATERIAL AT SMPN 20 BENGKULU - Tyas Yuliani Putri; Irwan Satria; Erik Perdana Putra (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
The purpose of this research is to ascertain whether or not puzzle media may improve students' cognitive learning results when used in conjunction with the image and picture model. A quasi-experimental study with a pre- and post-test control group design was conducted. Twenty-nine pupils made up the study's sample. They engaged in systematic stumbling in order to sample properly. The 15 multiple-choice questions on the pretest and posttest provided the raw material for this study. The SPSS 26.0 application was used to conduct a t-test analysis in the two groups. The data analysis revealed that the average value of class VII students' cognitive learning outcomes using the picture and picture model assisted by puzzle media was higher than the average value of students' cognitive learning outcomes using the conventional model, coming in at 84 77.34. When the t-test is performed at the 5% level of significance, a result of Sig. (2-tailed) 0.05 or 0.030 0.05 indicates that H0 is rejected and Ha is accepted. This demonstrates that the cognitive learning results of class VII pupils in the kingdom animalia content at SMPN 20 Bengkulu City are significantly influenced by the use of the image and picture models supplemented by media puzzles.